The Santa suit [large type] - Andrews, Mary Kay, 1954- (Thorndike Press large print core, 2021)
"When newly divorced Ivy Perkins buys an old farmhouse sight unseen, she is looking for a change in her life. The Four Roses, as the farmhouse is called, is a labor of love. At the top of a closet, Ivy finds an old Santa suit. In the pocket she finds a note from a girl who has one Christmas wish, for her father to return home from the war. Who wrote the note? Did the man ever come home? Ivy's quest brings her into the community at a time when all she wanted to do was be left alone and nurse her wounds. But the magic of Christmas makes miracles happen, and Ivy might find more than she ever thought possible: a family reunited, a mystery solved, and a second chance at love"--